Training and Assistance in Article Writing for Sinta Accredited Journals for Wonosobo Science MGMP - Desty Putri Hanifah; Sri Jumini; Parmin; Anisa Triyani; Mila Ariyani; Taufan Jannata; Sri Haryanto (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2024)
This service activity aims to improve teacher competence in writing scientific articles according to Sinta-accredited journal standards. Using the Participatory Action Research (PAR) method, this program involves a partnership with the Wonosobo Science MGMP in intensive training and mentoring. The focus of activities includes improving understanding of the structure of scientific articles, from writing abstracts to compiling bibliographies using Mendeley. The program results showed a significant increase in teachers' motivation and writing competence, as evidenced by producing five articles successfully submitted to Sinta 2 and 3 accredited journals. Participant satisfaction surveys showed overwhelmingly positive assessments, with most responses in the excellent and sound categories. The success of this program highlights the importance of intensive mentoring in teacher professional development, particularly in the aspects of research and scientific publications. Recommendations for future program development include expanding coverage, strengthening institutional collaboration, and developing a digital platform to support program sustainability. This program has the potential to have a long-term impact on the quality of education through improving teachers' research and publication capacity, instilling confidence and optimism in the audience.